2020
DOI: 10.3390/molecules25030494
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Heads as a Promising By-Product for Preparation of Food Gelatins

Abstract: Every year, the poultry industry produces a large number of by-products such as chicken heads containing a considerable proportion of proteins, particularly collagen. To prepare gelatin is one of the possibilities to advantageously utilize these by-products as raw materials. The aim of the paper was to process chicken heads into gelatins. An innovative method for conditioning starting raw material was using the proteolytic enzyme. Three technological factors influencing the yield and properties of extracted ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…If we compare the yield and properties of gelatins prepared under optimal process conditions with the results of our previous research onto the processing of chicken and hen by-products into gelatins, the following can be stated. The yield of gelatins from MDCM by-product (30–32%) is more or less comparable with the yields of gelatins prepared from chicken paws (18–38%) [ 27 ] and from chicken heads (20–36%) [ 30 ]; depending on the conditions of their preparation. However, compared to the yield of gelatins prepared from hen paws (8–21%) [ 35 ], the yield of gelatins from MDCM by-product is much higher (1.5–4.0 times).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…If we compare the yield and properties of gelatins prepared under optimal process conditions with the results of our previous research onto the processing of chicken and hen by-products into gelatins, the following can be stated. The yield of gelatins from MDCM by-product (30–32%) is more or less comparable with the yields of gelatins prepared from chicken paws (18–38%) [ 27 ] and from chicken heads (20–36%) [ 30 ]; depending on the conditions of their preparation. However, compared to the yield of gelatins prepared from hen paws (8–21%) [ 35 ], the yield of gelatins from MDCM by-product is much higher (1.5–4.0 times).…”
Section: Resultsmentioning
confidence: 71%
“…The results of gelatin yields from MDCM by-product are in certain cases lower; on the other hand, in certain cases higher, depending on the processing conditions, in comparison with the yields of gelatins prepared from chicken paws (18–38%) and from chicken heads (20–36%) using analogous biotechnological approach proposed by the authors [ 27 , 30 ]. From the available literature, it is possible to compare the results of gelatin yields from the same starting material treated with different processing methods as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D. Liu, Lin, and Chen (2001) and Huda, Seow, Normawati, and Aisyah (2013) reported that the collagen contents in the chicken and duck feet were 30.74% and 28.37% (wet basis), respectively, which are comparable to that extracted from fish waste material include skin, bone and fins with average of 50% (dry basis or 33.3% wet basis) reported by Nagai and Suzuki (2000). Jun, Lee, Lee, and Kim (2000) studied the feasibility of using chicken feet to replace cow hides, moreover, a number of studies were focused on poultry skins (Cliche, Amiot, Avezard, & Gariepy, 2003;Mhd Sarbon et al, 2013;Bichukale et al, 2018;Kim et al, 2020), feet (Almeida, da Silva Lannes, Calarge, de Brito Farias, & Santana, 2012;Yeo, Song, Ham, He, & Kim, 2013;Widyasari & Rawdkuen, 2014;Kuan, Nafchi, Huda, Ariffin, & Karim, 2016;Abedinia, Ariffin, Huda, & Nafchi, 2017), bones (Haroun, Beherei, & El-Ghaffar, 2010;Bichukale et al, 2018;Dewi;Yuliani, Awalsasi, & Jannah, 2019;Yuliani, Maunatin, Jannah, & Fauziyyah, 2019), mechanically deboned residue (Fonkwe & Singh, 1997;Rammaya, Ying, & Babji, 2012;Rafieian et al, 2013;Rafieian, Keramat, & Shahedi, 2015) and processing by-product (Almeida, da Silva, da Silva Lannes, de Brito Farias, & Santana, 2013;Gál et al, 2020) to develop gelatin as an alternative source for mammalian gelatin.…”
Section: )mentioning
confidence: 99%
“…However, Dewi Yuliani, Maunatin, Jannah, and Fauziyyah (2019) obtained gelatin with favorable physicochemical properties from broiler chicken bones using different concentrations and treatment times of 8-10% phosphoric acid. (Gál et al, 2020), (Ee et al, 2019) Chicken deboned residue (Masood & Chen, 1995), (Rammaya et al, 2012), ( Rafieian et al, 2013), (Rafieian et al, 2015), (Erge & Zorba, 2018) Turkey deboned residue Fonkwe and Singh (1997) Chicken feet (Jun et al, 2000), (Almeida et al, 2012), (Rahman & Jamalulail, 2012), (Almeida et al, 2013), ( Almeida et al, 2013), (Choe & Kim, 2018) ( Saenmuang et al, 2019), (Santana et al, 2020) Duck feet (Yeo et al, 2013), (Park et al, 2013), (Y. H. Kuan, Nafchi, Huda, Ariffin, & Karim, 2017), (Abedinia et al, 2017) Bovine hide splits are ordinarily treated with acid for 48-72 h. It must be noticed that ensuing the acid conditioning, the extraction, likewise, is completed in an acid condition. After this treatment, pH is expanded to 2-4 by including alkali.…”
Section: Acid Treatmentmentioning
confidence: 99%